Analisis Yuridis Hukum Pidana Militer dalam Perkara Nomor 231-K/PM.II-08/AD/X/2020 - Kirana Adhelia Putri; Nabila Zalfa; Pramudita Antasia; Diva Pramesti Islami; Nabila Adifia Azzahra; Irwan Triadi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The military court as the administrator of judicial power has a role in enforcing the law against perpetrators of LGBT crimes so that the Panel of Judges hearing the case is able to provide good and complete considerations according to the facts at trial through their legal considerations. One of them is the case of Arnold Martumoga Siburian, in the decision with Case Number 231-K/PM II-08/AU/XII/2020, who was proven to have committed acts of same-sex sexual relations. This research uses normative legal analysis, where the law is usually stated in law or made into laws or principles that become a moral code that is considered appropriate by society. A military person who commits an immoral crime is not only threatened with violating the criminal law, but also violating the disciplinary law. This means that in addition to being threatened with criminal penalties, they will also be subject to the Military Discipline Law depending on how serious the offense committed by the military member is. A military member who engages in immoral criminal acts not only risks breaking the criminal law, but also simultaneously breaking the law. discipline. This means that, apart from being threatened with criminal charges, they will also be subject to sanctions under the Military Discipline Law, depending on the level of escalation of the criminal act committed by the military member. Evidence of conversations on an application and testimony from witnesses shows that there are activities that support the alleged violations committed by the perpetrator. Based on the TNI Commander's Telegram Letter which regulates the prohibition on TNI Soldiers who commit homosexual or Lesbian immoral acts, the perpetrator was sentenced to be dishonorably discharged from TNI soldier service.